Electromagnetic and mechanical properties of soft magnetic cement composite for airport runway induction heating: Experimental and simulation analyses. (15th January 2022) - Gu, Gonghui; Chen, Feng; Ma, Tao; Xu, Fang; Yang, Dengfeng
Abstract: Soft magnetic material can concentrate magnetic flux and reduce electromagnetic loss during an induction heating process. The motivation of this work is to develop a soft magnetic cement composite (SMCC) material that can be used to dramatically improve the energy-saving rate during the induction heating process of airport runway. SMCC specimens were prepared by mixing iron powders with different particle sizes into cement paste under room temperature. The important influences of iron powder size on the electromagnetic and mechanical properties of SMCC were analyzed. Results show that the particle size of iron powders should be above a certain level during the material design of SMCC, so as to limit the formation of micro pores and demagnetization fields within the composite, guaranteeing thus the magnetic and mechanical performances of SMCC. Besides, the properly designed SMCC material can meet the mechanical requirements of airport runway and reduce the energy consumption by 15.6% during a single induction heating process, indicating great value and potential of cleaner production.